Factors related to spiritual coping in adolescents with cancer based on the "Reed self-transcendence theory" - Hakimeh Eskandari Sabzi; Azam Shirinabadi Farahani; Maryam Rassouli; Leila Khanali Mojen; Raziyeh Beikmirza; Maryam Heidari (Tehran University of Medical Sciences, 2021)
Background & Aim: Being diagnosed with cancer during adolescence can cause disabilities and disrupt the achievement of important tasks during this period. Given the complex spiritual issues that adolescents face, emphasizing them can provide a unique framework for understanding and coping with illness. The purpose of this study was to determine factors related to spiritual coping in adolescents with cancer based on the "Reed self-transcendence theory". Methods & Materials: In this descriptive, correlational study, 270 adolescents with cancer referred to hospitals affiliated to Shahid Beheshti University of Medical Sciences in Tehran in 2018-19 were selected using the convenience sampling method. Data was collected using the demographic and clinical characteristics questionnaire, the "Adolescents Spiritual Coping Scale", "Adolescents Hope Scale", "Self-transcendence Scale: Adolescent version and "Adolescent Coping Scale". Data was analyzed using the SPSS software version 19 through descriptive statistical methods, Kruskal-Wallis test, Kolmogorov-Smirnov test, the Spearmanchr('39')s correlation test and Path analysis. Results: Based on the Spearman correlation coefficient, the relationship of hope (rs=0.440, P<0.001), coping (rs=0.149, P=0.015) and self-transcendence (rs=0.143, P=0.019) was positive and significant with the spiritual coping. Also, the results of path analysis of the Reed self-transcendence model showed that hope and self-transcendence had direct effects on spiritual coping and coping had an indirect effect on spiritual coping in adolescents through the intermediate variable of self-transcendence. Conclusion: The variables hope, coping and self-transcendence are the factors related to spiritual coping in adolescents with cancer, and the model of self-transcendence in Iranian adolescents with cancer is appropriate. Therefore, nurses as the first providers of care can enhance spiritual coping in adolescents by focusing on this model and manipulating its various variables.